Analisis Kemampuan Pemecahan Masalah Matematika Geometri PISA pada Siswa Kelas VIII Semester Genap SMP Negeri 1 Mojosongo Tahun 2015/2016 - Sulistyaningsih, Eni; , Prof. Dr. Budi Murtiyasa, M.Kom (2016)
This study aimed to describe the ability of geometrical mathematics problem solving based on PISA and its percentage. This research is a qualitative descriptive. Subjects of this study is class VIII E SMPN 1 Mojosongo amounting to 24 students. The data collection technique uses the test method, interviews, observation, and documentation. Data validation is done by triangulation method by comparing data from the test method, interviews, and documentation. Data analysis techniques is performed by stage data reduction, data presentation, verification and conclusion. The result of this research shows that the mathematical ability of the first level is 38.79%, the second level is l6.03%, the third level is 0.86%, the fourth is 13.79%, the fifth level is 30,17%, the sixth level is 10.34%. The results indicates the general ability of students in solving mathematical problems is at the first level and the fifth level, This can be seen from the ability of problem solving, the ability of process component as well as mathematical context in PISA.